RATIONAL USE OF MEDICINES BASED ON SHARIA PRINCIPLES IN SELF-MEDICATION AT SIROTO PHARMACY BANYUMANIK SEMARANG - Rahma, Dinda; Rosyid, Abdur; Widyaningrum, Naniek (Gamma Publishing, 2025)
In Islamic teachings, Muslims are encouraged to make efforts (ikhtiar) in facing various challenges, including when experiencing illness. Self-medication is one form of ikhtiar that is carried out independently to treat mild symptoms using over-the-counter or limited over-the-counter medicines. Rational drug use is key to ensuring the safety and effectiveness of treatment. The World Health Organization (WHO) defines rational drug use as the provision of medicines according to the patient's clinical needs, in the right dose and duration, and at an affordable cost. for Muslims, in addition to rationality, the halal aspect is also an important consideration in the use of medicines. The halal-thayyib principle, as explained in the Qur'an Surah Al-Baqarah verse 168, emphasizes the importance of choosing medicines that are not only safe and effective but also halal. however, the public's level of knowledge about the halal status of medicines is still relatively low. education about halal medicines is highly necessary, especially among Muslims, to increase awareness and understanding. this study aims to determine the level of public knowledge regarding the rational use of medicines based on sharia principles in self-medication practices. the method used is descriptive with a questionnaire instrument distributed directly to respondents. the results show that the majority of respondents understand the concept of rational drug use and prefer to obtain medicines from pharmacies and doctors. in terms of sharia, the understanding of the halal and haram concept in medicines is relatively high, but awareness of ingredients such as gelatin and alcohol remains low. therefore, more intensive education on the halal aspects of medicine use is needed so that Muslims can be more selective in accordance with Islamic law. Ask ChatGPT